KONFLIK TANAH ULAYAT ANTARA KAMANAKAN MALAKOK DENGAN NINIAK MAMAK SUKU TOBO DI NAGARI PADANG LAWEH KECAMATAN KOTO VII KABUPATEN SIJUNJUNG - Ningsih, Welda; Anggreta, Dian Kurnia; Fitlayeni, Rinel (Pendidikan Sosiologi, 2013)
This paper describes the background of communal indigenous land conflicts between kamanakan malakok with niniak mamak Tobo tribe, in Nagari Koto Padang District VII Laweh Sijunjung district. Conflict begins with the presence of communal land area of ± 2500 m² (1/4hektar) located in Ganting (SMP 8 Nagari Padang Simpang Laweh) Jorong Koto Padang Laweh which is belongs niniak mamak Tobo tribe of the land has not been tilled by niniak mamak and still empty. However kamanakan malakok fence and mengarap without the permission and knowledge of niniak mamak triggering conflict. The research problem is how the background to the conflict and resolution of conflicts between kamanakan malakok with niniak mamak Tobo tribe in Nagari Padang Laweh. The purpose of this study describes the background to the conflict and the resolution of conflict between kamanakan malakok with niniak mamak Tobo tribe in Nagari Koto Padang Laweh District VII. In this study, the author uses the theory of Lewis Coser, to avoid conflicts from the sharper the necessary safety valve.The approach used in this study is a qualitative approach with descriptive type to provide a detailed picture of the reality under study. Data was collected through observation and interviews. Informants were taken by sampling porposive. Based on the results of research conducted, communal land conflicts caused by malakok nephew who worked and fencing of communal land without the permission and knowledge of the Tobo tribe niniak mamakresulting land conflict issues. While the form of conflict resolution through deliberation and consensus between the two sides, conflict is not resolved by the prince of the tribe resulting in the issue resolved through official organizations, the wali nagari the prince of the tribe and last through the police, after receiving the decision of the police, found both parties and reach an agreement by dividing 2 lands which are written above the letter of agreement, signed byboth parties.